STRUCTURAL SYSTEMS OF HIGH-RISE BUILDINGS - Pershakov, Valeriy; Bieliatynskyi, Andrii; Bilyk, Sergiy; Bakulin, Yevgen; Pylypenko, Oleksandr; Bolotov, Georgiy; Akmaldinova, Oleksandra; Martynenko, Ivanna; Reznyk, Oleksandr (Proceedings of National Aviation University (archive), 2020)
The article is devoted to topical issues of researching structural designs as a component of high-rise buildings structural system, which form an architectural image and a volumetric three-dimensional structure, consisting of a set of interconnected structural elements that, working together, provide the strength of the volumetric structure, spatial rigidity and overall stability of the object. High-rise buildings use different structural designs, consisting of vertical elements (columns, walls, nuclei, diaphragms etc.) and horizontal elements (floors, beams, slanting belts etc.). Horizontal load-bearing structures of high-rise buildings, are, as a rule, of the same type and represent a rigid reinforced concrete disk (monolithic, precast-monolithic, precast). Horizontal structures carry vertical and horizontal loads and transmit them to load-bearing structures and foundations. To reduce wind effect, aerodynamically efficient cylindrical, pyramidal or prismatic shape of the building is chosen. The high-rise buildings designs have their own specificity, which greatly influences the three-dimensional planning and architectural and design decisions. These features include: significant loads on load-bearing structures; unequal loads on structural elements; high wind load as a horizontal component; problems of joint work of load-bearing structures made of steel and concrete; impact of natural factors (seismic, atmospheric, aerodynamic); influence of technogenic factors (vibrations, noise, accidents, fires, sabotage acts, local destruction); heightened requirements for fire safety and environment control systems; complex engineering and technical support.